Organic Waste Crushing Machine Automation in Eco Enzyme Production - Syamsudduha Syahrorini; Shazana Dhiya Ayuni; Fariz Zulfiryansyah; Izza Rosyidah (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
In 2025, Indonesia has launched a zero-waste program. Towards a zero-waste program, of course, the community is given awareness in sorting and processing waste. Waste management is a common problem in urban or rural areas, along with the increase in population and people's lifestyles. Waste problems that are not handled properly can cause environmental problems (pollution of air, soil, and water) and public health. Based on the origin, waste is divided into organic and inorganic waste; organic waste is produced from biological materials that can be degraded by microbes or are biodegradable, or waste from fruit, vegetable, and leaf residues. This organic waste is the majority of the waste generated from households, so it is necessary to think about how to process it that is beneficial and efficient. One of these organic waste processing is processed into Eco enzymes, namely processing organic waste with molasses and water in a ratio of !:3:10. The organic waste processing process is first chopped to become a small part to facilitate the fermentation process. The automation of this chopping machine uses Arduino as a microcontroller, a load cell as a measure of the weight of organic waste, an electric motor as a driving force, a solenoid door lock as a lock for the organic waste load before grinding, and a knife as an organic waste count. The purpose of making this tool is to help chop organic waste in the process of processing eco enzymes. The research results on the automation of this organic waste chopper machine loadcell with a load of 1 Kg runs well; the solenoid door lock can hold organic waste to work well. The research results on the motor for upper milling are given a large torque equipped with a downward knife position and a pillow block so that the motor does not shake.